(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Alalia is the speech of a child in the mother’s womb or at an early stage of development organic injury of the speech sphere of the cerebral cortex before its formation. It is convenient to eliminate speech defects and It is important to use effective methods. Alalia in children diagnosis of speech disorders in the process of working on a speech disorder. The article talks about the methods of shaping the speech of children with Alalia speech disorder.